ALTERNATIVE SCIENCE GAME FOR INCREASE COGNITIVE ABILITY OF EARLY AGE CHILDREN - Angraeny Unedia (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of this study was to improve children's cognitive ability of Group A in ECE Yasmin Jember, which was focused on (1) the ability to recognize simple concepts in daily life; (2) the ability to observe and curiosity; (3) the ability to classify; (4) the ability to relate cause and effect. This study was conducted by using qualitative descriptive approach. 11 children of Group A in ECE Yasmin Jember were subject of this study. Data collection techniques used observation, interview, and documentation. Miles and Huberman model were chosen as data analysis techniques which has three steps; data reduction, data display, and drawing or conclusion (verification). Based on research and data analysis during learning process activities known that there were 6 children who have been able to show interest in learning and problem solving while 45% or 5 of the 11 children required motivation and guidance in terms of expressing curiosity and solving problems when they were in science center. This happened because previously 5 children have ever been attended school at other, so they did not follow the whole same learning activities in ECE Yasmin Jember.